Data Transfer Security in IoT Communication Based on Attribute-Based Cryptography - Abidullah, Adel; Rahmani, Khoshal Rahman; Wadeed, Wali Mohammad; Hakimi, Musawer (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Due to the drastic growth, the Internet of Things (IoT) has become an inevitable form of human life. However, IoT communication is subjected to a vast range of security breaches in the vulnerable environment, which leads to the demand for appropriate technology security issues in IoT communication. The cryptography technique exhibits effective security characteristics that promise promising results for identifying security breaches in IoT. This paper proposes attribute-based elliptical curve cryptography (ATB_ECC) to improve security in IoT communication. IoT devices perform communication to overcome security issues in IoT based on defined attributes of access points. Attributes are involved in the characteristics of trusted nodes in the network. The cryptography technique utilizes Elliptical Curve Cryptography (ECC) to transmit messages securely in the IoT environment. Through integrating attribute factors and cryptography techniques, the IoT network can distinguish variations in the active data communication and threats in the IoT network. Simulation performance is examined for different critical structures, such as low, medium, and high. The proposed ATB_ECC is examined for attack prediction scenarios considering real-time servers. The examined results stated that the proposed ATB_ECC has effectively prevented attacks, especially brute force attacks. Analysis of results stated that low-key structure exhibits minimal complexity, but the security level is minimal. A high-key structure consumes vast energy and has increased complexity, but the security is significantly improved. The comparative analysis of various key structure results illustrated that the proposed attributes-based ECC exhibits improved performance at 15% for throughput.